Papel do estresse oxidativo e de vias pró-inflamatórias na osteonecrose dos maxilares induzida por bisfosfonatos em ratos - Ferreira Júnior, Antonio Ernando Carlos (2020)
Bisphosphonates are drugs commonly used in the treatment of bone disorders and mainly in the treatment of bone metastases during antineoplastic therapy. As an adverse effect, these drugs are associated with the development of bisphosphonate-associated jaw ostechionecrosis (OMB), a difficult-to-treat condition with poorly understood pathogenesis. However, it is suggested that inflammatory mechanisms may be associated with increased cytokine expression and participation of specific immune cell groups. Thus, the objective of the present study is to delineate proinflammatory mediators pathways including the participation of oxidative stress in the pathogenesis of experimental OMB. Fifthy-four (Six per group) Male Wistar rats (180-220g) were submitted to four weekly venous injections of sterile saline or zoledronic acid (AZ) 0.20 mg / kg, associated or not with blockade of TNF-α (infliximab 0,5 mg / kg), iNOS (aminoguanidine 50 mg / kg) and COX-2 (celecoxib 16 mg / kg). Subsequently, they were submitted to left lower first molar extraction (day 49). After 70 days, euthanasia was performed, where the organs (liver, spleen, kidneys and stomach) and jaws of the animals were removed and weighed. The latter were hemisected (left and right sides) and submitted to radiographic, histological, histomorphometric analysis (polymorphonucellar, mononucellar count, number of empty osteocyte and osteoclast gaps) and immunohistochemistry for the markers COX-2, Tumor Necrosis Factor. Alpha (TNF-α), Interleukin (IL) -1β, IL-6, Caspase-3, RANK, RANKL and OPG by the streptavidin-biotin-peroxidase method. Myeloperoxidase (MPO), Nitrite / nitrate, Glutathione and Malanoaldehyde levels were also verified. As a result, radiographically the saline group presented the area at the repaired extraction site at the end of the experimental period, whereas the groups treated with zoledronic acid, the values obtained from the radiolucent area were significantly higher than the saline group (p <0.001), thus obtaining areas suggestive of osteonecrosis without differences even between the different blocks (p = 0.098). After histomorphometric analysis, the number of neutrophils in the saline group (3 ± 1) was significantly lower than in the zoledronic acid group (373± 85) (p <0.05). The animals co-treated with aminoguanidine showed a significant reduction in the number of neutrophils (140 ± 18) in relation to the AZ group (p <0.05). In addition, the same aminoguanidine-treated group (233 ± 12) increased the number of mononucellars compared to the AZ-treated group alone (168 ± 29). The number of apoptotic osteoclasts and empty osteocyte gaps showed no differences after the different blocks. In immunohistochemical analysis, the zoledronic acid group showed significant increase in TNF-α (p <0.001), IL-1β (p <0.001), IL-6 (p = 0.007), iNOS (p = 0.003), COX- 2 (p = 0.003), NF-κB (p <0.001), RANKL (p = 0.020), OPG (p = 0.001), TRAP (p<0.001) and Caspase-3 (p = 0.001) relative to the saline group. In addition, higher dosages of MPO (p <0.005), Glutathione (p = 0.025) and Malanoaldehyde (p = 0.027) were also observed in the AZ group compared to the saline group. After blockade, a significant decrease was seen in the AZ-treated group for IL-1 expression in the tocilizumab cotreated group (p = 0.021), for IL-6 in the tocilizumab co-treated group (p = 0.041), TNF-α in the infliximab co-treated group (p <0.001), iNOS in the aminoguanidine co-treated group (p = 0.042) and COX-2 in the aminoguanidine (p = 0.012). ) and celecoxib groups (p = 0.038), with no significant differences for NF-κB expression among all groups receiving AZ (p = 0.091). Thus, it was concluded that partial blockages of TNF-α, IL-6 and COX-2 through infliximab, tocilizumab and celecoxib, respectively, did not interfere with the radiographic and histological characteristics of OMB. However, the blockade of oxidative stress through the administration of aminoguanidine, altered inflammatory aspects present (polymorphonucellar / mononuclear ratio), but without repercussion in the number of cells with apoptosis signs or empty osteocyte gaps.